Modelling contaminant transport in generic landfills for decommissioning waste from German nuclear power plants. (May 2016) - Seher, H.; Navarro, M.; Artmann, A.; Larue, J.; Roloff, R.; Weiß, D.
Abstract: The German decision to phase out nuclear power will increase the quantity of very low level waste (VLLW) from nuclear power plant (NPP) decommissioning in the near future, which will cause a capacity shortage of landfills. As a likely consequence, landfills will have to be constructed that are exclusively built for decommissioning waste without addition of municipal waste, and assessments for such types of landfills are not available in Germany. The present study investigates flow and transport processes in generic landfills that only contain decommissioning waste. The generic landfills comply with German technical standards such as the Landfill Ordinance. Simulations of contaminant transport are performed using the codes SiWaPro DSS and SPRING. The simulations show that Sr-90 is the first radionuclide that leaves the landfill due to its low sorption in the waste body. In contrast, no release of Cs-134, Cs-137 and Am-241, which have higher sorption coefficients, was simulated. Our work also shows that three-dimensional modelling of flow and transport is required if the landfill has a lateral drainage. Results suggest that the migration of radionuclides into the environment could be reduced by installing a drainage layer with high sorption capacity on top of the landfill's bottom seal. Sorption of Sr-90 within this drainage layer would delay the release of Sr-90 from the landfill, thereby giving more time for the Sr-90 decay inside the landfill. Highlights: We investigate flow and transport processes in landfills. The considered landfills consists of wastes from decommissioning of nuclear facilities in Germany. The deposited waste was not mixed with municipal waste. We describe the characteristics of radionuclide release.